Faktor-faktor yang mempengaruhi Work Family Conflict di Industri Perhotelan Jakarta - Imaad Athallah Zayyan; Dita Oki Berliyanti (Astina: Jurnal Ekonomi Utama, 2024)
This research aims to analyze the influence of Supervisor Bullying, Perceived Organizational Support, Social Support, Work Overload, and Work Stressors on Work Family Conflict (WFC) in the Jakarta hotel industry. This research uses quantitative methods with a survey research approach, where data is collected through online questionnaires filled out by 240 hotel industry employees in Jakarta. The sampling technique used was purposive sampling. The questionnaire used consisted of 48 items representing six research variables. Data analysis was carried out using descriptive statistics and Structural Equation Modeling (SEM) with SPSS version 25. The research results showed that Work Overload had the greatest influence on Work Family Conflict. Supervisor Bullying and Work Stressors were proven to have a positive and significant influence on Work Family Conflict, while Perceived Organizational Support and Social Support did not show a significant influence. These findings provide insight into the factors that influence the balance between work and family life of employees in the hospitality industry.